Observing A Head of Study Program’s Leadership Style at an Islamic-based University in Indonesia - Andi Patimbangi; Kasmah Kasmah (STAI Hubbulwathan Duri, 2022)
Various internal conflicts in education management generally occur due to poor leadership. Therefore, good leadership and governance are needed. This exploratory case study investigates the practices of a head of the study program at an Islamic-based higher education institution in South Sulawesi, Indonesia. Using the framework of Total Quality Management (TQM), a movement philosophy that aims to help solve personal problems in education, especially leadership, this study examines how this leader implements those principles as his typical leadership style. In this regard, competence, experience, and personal character must be considered in preparation for development. These four aspects can affect performance and leadership roles in leadership, organizational, and public roles. The data of this study was collected from the observation conducted in an Islamic based higher institution in South Sulawesi. Meanwhile, to analyze the data, a thematic analysis method was used. The study's findings are divided into four main categories, namely, characteristics, operational leadership, organizational leadership, and public leadership. Implications and future recommendations are also provided.